Nurse participation in legal executions: An ethics round-table discussion. (November 2018) - Shields, Linda; Watson, Roger; Darbyshire, Philip; McKenna, Hugh; Williams, Ged; Hungerford, Catherine; Stanley, David; Ben-Sefer, Ellen; Benedict, Susan; Goodman, Benny; Draper, Peter; Anderson, Judith
A paper was published in 2003 discussing the ethics of nurses participating in executions by inserting the intravenous line for lethal injections and providing care until death. This paper was circulated on an international email list of senior nurses and academics to engender discussion. From that discussion, several people agreed to contribute to a paper expressing their own thoughts and feelings about the ethics of nurses participating in executions in countries where capital punishment is legal. While a range of opinions were presented, these opinions fell into two main themes. The first of these included reflections on the philosophical obligations of nurses as caregivers who support those in times of great need, including condemned prisoners at the end of life. The second theme encompassed the notion that no nurse ever should participate in the active taking of life, in line with the codes of ethics of various nursing organisations. This range of opinions suggests the complexity of this issue and the need for further public discussion.